2013
DOI: 10.17795/rijm14849
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA in Mesenchymal Stem Cells Differentiation Into Osteoblasts

Abstract: Context: miRNAs can regulate the expression of genes by interfering in their mRNAs, acting as key regulators of diverse cellular activities. Osteoblast differentiation is an important process for skeletal developments and involves several mechanisms regulated by miRNAs. The data for this article was collected from recently published peer reviewed articles on role of miRNA in osteoblasts growth and differentiation. Evidence Acquisition: In this review, our understanding of bone remodeling has been highlighted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Tissue development is spatiotemporally regulated by transcription factors and noncoding RNAs including microRNAs, which either stimulate or inhibit the expression of target genes in a cell type-specific manner [25]. Several factors negatively regulate bone formation including microRNAs such as miR-378, miR-138, and miR-182 [26, 27] and transcription factors such as NFE2 [2], GATA4 [28], and HOXC8 [29] as well as p53 as a tumor suppressor [30]. Previously, we have demonstrated that Tbx20 has cardiogenic effects [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue development is spatiotemporally regulated by transcription factors and noncoding RNAs including microRNAs, which either stimulate or inhibit the expression of target genes in a cell type-specific manner [25]. Several factors negatively regulate bone formation including microRNAs such as miR-378, miR-138, and miR-182 [26, 27] and transcription factors such as NFE2 [2], GATA4 [28], and HOXC8 [29] as well as p53 as a tumor suppressor [30]. Previously, we have demonstrated that Tbx20 has cardiogenic effects [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miRNAs have emerged as important regulators in tumorigenesis, viral infection, and cell differentiation [17]. Hence, various miRNAs have been used for differentiation of osteogenesis [18,19,20]. It was reported that miRNA-148b (mir148b) can be used to induce osteogenic differentiation by blocking the Noggin signal [16,21,22].…”
Section: Introductionmentioning
confidence: 99%